Comparison of once a day rifaximin to twice a day dosage in the prevention of recurrence of hepatic encephalopathy in patients with chronic liver disease. Issue 9 (September 2015) - Khokhar, Nasir; Qureshi, Muhammad Omar; Ahmad, Shafiq; Ahmad, Aiza; Khan, Hamza Hassan; Shafqat, Farzana; Salih, Muhammad
Abstract Background Rifaximin has been used for prevention of recurrence of hepatic encephalopathy in twice a day dosage. The drug is expensive and lower dising may be possible. Objective To determine the efficacy of rifaximin once a day dose in the prevention of hepatic encephalopathy (HE) in patients with liver cirrhosis as compared with twice daily dose of rifaximin. Methods This Randomized control trial was carried out at the Department of Gastroenterology and Hepatology, Shifa International Hospital, Islamabad, Pakistan from November 2012 to February 2014. Patients with known chronic liver disease with at least one episode of HE in the past were randomized to group A (rifaximin 550 mg OD) and group B (rifaximin 550 mg BD), after fulfilling the inclusion criteria. Each patient was followed for 6 months for any episode of HE. Patients in each group were identified for any breakthrough episode of encephalopathy during this period. Data were analyzed using SPSS version 16. Chi‐squared test and t‐test were applied where required to determine the significant difference between the two groups. Results There were a total of 306 patients: 128 patients in Group A while 178 in group B. Majority of patients (75.81%) had hepatitis C virus with mean age of 52.30 ± 9.92, MELD score 13.58 ± 8.3, and 55.22% were in Child–Pugh B. Eighty‐one patients had an episode of HE during the study period. There were 27 patients in group A and 54 patients in group B with breakthrough episode of HE (P = 0.088). Conclusion This study suggests that there is no significant difference in rifaximin once a day or twice daily dose in preventing HE.